Catha edulis Forsk (khat) reduces spontaneous and rewarded alternation in female mice. (December 2020) - Murithi, Caroline K.; Kabaru, Jacques M.; Patel, Nilesh B.
Graphical abstract: Highlights: Khat is a widely used plant-based psychostimulant. Administration of khat leads to disruption of spatial working memory in mice. It promotes in mice perseverative behavior rather than alternation behavior. Khat treated mice also show right side position preference. Abstract: Around 10 million people chew the fresh leaves and twigs of Catha edulis Forsk (khat), which synthesize cathinone, for its psychostimulatory effect. Several studies have reported that regular khat users show executive and cognitive dysfunction, such as impaired inhibitory control and poor performance on memory tests. In this study, the effect of fresh khat extract (100 and 250 mg/kg) on spatial working memory and short-term memory in mice was assessed using spontaneous and rewarded alternation T-maze tests. In the spontaneous alternation test, mice treated with fresh khat extract decreased their spontaneous alternation level to around chance level, and it remained at this level over the 7 days of khat administration and testing. On testing after a 7-day khat free period, the previously khat treated mice showed alternation level above chance but below their pre-khat alternation level. In the rewarded alternation test, acute treatment with khat caused the mice to alternate well below chance level, and then over the next 3 days of khat treatment, the alternation level increased. After a 2 and 9-day khat-free period, the previously khat treated mice alternated above chance level but below their pre-khat level. In both these tests, the mice did not show any position preference before khat treatment; however, during the khat treatment, the mice showed a right side tendency. The results show that khat treatment causes persistent changes in alternation behavior and promotes perseverative behavior, presumably due to its effect on the neural circuits activity and the neurotransmitters and promotion of position preference.